Validation and Reliability Testing of the Child Oral Impacts on Daily Performances (C-OIDP): Cross-Cultural Adaptation and Psychometric Properties in Pakistani School-Going Children - Farooq Ahmad Chaudhary; Azhar Iqbal; Muhammad Danial Khalid; Nouman Noor; Jamaluddin Syed; Muhammad Nadeem Baig; Osama Khattak; Shahab Ud Din (MDPI AG, 2022)
Background: This study aimed to develop an Urdu version of Child-Oral Impact on Daily Performance (C-OIDP) and assess its reliability and validity for children's oral health-related quality of life (OHRQoL) assessment in Pakistan. Methods: A total of 200 school-going children aged 11-14 were recruited from two public schools. For the adaptation process, the original English version of C-OIDP was translated into Urdu, reviewed by an expert committee, back-translated into Urdu, and then reviewed again by the same expert committee and pilot tested on 10 children. A clinical examination was carried out to record dental and gingival status followed by a face-to-face interview to measure oral health-related quality of life in children using C-OIDP-U. Reliability, internal consistency, construct and discriminant validity were assessed. Results: The Cronbach's alpha for C-OIDP-U was 0.69, the mean C-OIDP-U score was 10.2 ± 8.1 and 77.3% of the children reported at least one oral impact. Eating (40.3%) and difficulty in cleaning mouth (38.7%) were the two most impacted daily performances. For construct validity, the associations were significant between the C-OIDP-U score and all subjective oral health measures (p < 0.001). For discriminant validity, a significant association was observed between the C-OIDP-U score and clinical oral variables, children with DMFT + dmft ≥ 1, Gingival index > 1 and having malocclusion reported a higher C-OIDP-U score when compared to their counterparts. Conclusion: This study showed that C-OIDP is a valid, reliable and efficient instrument of OHRQoL for use in Pakistani children.